2013
DOI: 10.1542/peds.2012-3643
|View full text |Cite
|
Sign up to set email alerts
|

Trisomy 18 and Complex Congenital Heart Disease: Seeking the Threshold Benefit

Abstract: A prenatal diagnosis of ductal-dependent, complex congenital heart disease was made in a fetus with trisomy 18. The parents requested that the genetic diagnosis be excluded from all medical and surgical decision-making and that all life-prolonging therapies be made available to their infant. There was conflict among the medical team about what threshold of neonatal benefit could outweigh maternal and neonatal treatment burdens. A prenatal ethics consultation was requested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 16 publications
1
18
0
Order By: Relevance
“…While our study provides evidence that there is clinician support of the discussion of the option cardiac surgery, many clinicians expressed disagreement with offering cardiac surgery in light of the lack of outcome data and ethical principles such as nonmaleficence, beneficence, and justice. These findings support and further validate previous studies (Boss et al, ; Graham, ; Janvier et al, ) that have identified the same concerns and were unsurprising, as the ethical nature of such surgery is an important and recurrent topic in discussions between clinicians and families when deciding if cardiac surgery is appropriate (Janvier et al, ). Many hospitals offer access to an ethics committee consult, which may be warranted to aid in parsing out these complex ethical issues.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…While our study provides evidence that there is clinician support of the discussion of the option cardiac surgery, many clinicians expressed disagreement with offering cardiac surgery in light of the lack of outcome data and ethical principles such as nonmaleficence, beneficence, and justice. These findings support and further validate previous studies (Boss et al, ; Graham, ; Janvier et al, ) that have identified the same concerns and were unsurprising, as the ethical nature of such surgery is an important and recurrent topic in discussions between clinicians and families when deciding if cardiac surgery is appropriate (Janvier et al, ). Many hospitals offer access to an ethics committee consult, which may be warranted to aid in parsing out these complex ethical issues.…”
Section: Discussionsupporting
confidence: 89%
“…In our study, clinicians' attitudes were examined surrounding common themes that have emerged in previous literature on this topic (Boss et al, ; Graham, ; Janvier et al, ; Janvier & Watkins, ). While our study provides evidence that there is clinician support of the discussion of the option cardiac surgery, many clinicians expressed disagreement with offering cardiac surgery in light of the lack of outcome data and ethical principles such as nonmaleficence, beneficence, and justice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though cardiac complications are a major cause of death in PS and ES patients, a large retrospective study demonstrated that cardiac interventions are less common than procedures not related to cardiac pathology, including gastrointestinal, orthopedic, and facial interventions [11]. There is currently no consensus among medical professionals regarding the advisability of operating on CHD in patients following the prenatal diagnosis of PS and ES [1]. Therefore, not surprisingly, PS and ES infants with CHD who survive to birth often die early in life due to heart failure secondary to cardiac malformations.…”
Section: Discussionmentioning
confidence: 99%
“…However, over the past 15 years, there have been a number of manuscripts published in the medical literature describing the outcomes of infants with trisomies 18 and 13 who underwent cardiac surgical repair . These reports have been accompanied by the formation and/or strengthening of advocacy and support organizations for patients and families with trisomies . These events have empowered parents of babies with trisomy 18 or 13 to initiate discussions about congenital heart surgery, sometimes contacting the offices of pediatric cardiovascular surgeons directly.…”
Section: Introductionmentioning
confidence: 99%